2001
DOI: 10.1023/a:1010215516226
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have shown earlier that microsomal cytochrome b5 can form a specific complex with mitochondrial cytochrome P450 (cytochrome P450scc). The formation of the complex between these two heme proteins was proved spectrophotometrically, by affinity chromatography on immobilized cytochrome b5, and by measuring the cholesterol side-chain cleavage activity of cytochrome P450scc in a reconstituted system in the presence of cytochrome b5. To further study the mechanism of interaction of these heme proteins and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Recently, the heterologous expression of HMW-holo-b 5 in microorganisms has been achieved, allowing the production of large amounts of the different forms of recombinant b 5 (33,34,(76)(77)(78)(79)(80)(81)(82)(83). This approach has been used to study, for example, the role of specific amino acids of b 5 by sitedirected mutagenesis (84,85), the mechanism of interaction of the C-terminal sequence of b 5 with membrane structures (86), and also the mechanism of electron transfer (87).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the heterologous expression of HMW-holo-b 5 in microorganisms has been achieved, allowing the production of large amounts of the different forms of recombinant b 5 (33,34,(76)(77)(78)(79)(80)(81)(82)(83). This approach has been used to study, for example, the role of specific amino acids of b 5 by sitedirected mutagenesis (84,85), the mechanism of interaction of the C-terminal sequence of b 5 with membrane structures (86), and also the mechanism of electron transfer (87).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting Analysis. Immunoblotting analysis was carried out as described previously (34), using antibodies against rat liver microsomal HMW-b 5 . Immunoblotting analysis of the His67Ala mutant of b 5 was used to estimate the level of expression of the mutant protein in E. coli and for detection of the mutant b 5 during the purification procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, both Th 4+ and UO 2 2+ ions reduce the oxy-form of Hb at a high concentration of >100 µM [40]. Cyt b 5 is a small membrane binding heme protein, and its heme-binding domain is highly negatively charged by a series of acidic residues, forming an "acidic" cluster [41][42][43]. Spectroscopic study showed that uranyl may bind to the surface of Cyt b 5 with a binding affinity of K D = 10 µM, and molecular modeling study suggested a possible uranyl binding site at surface residues, Glu37 and Glu43 (Figure 2a) [44,45].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…Expression vectors pCWori+ and pT7 were kind ly provided by Dr. R. W. Estabrook (UT Southwestern Medical Center, USA). For expression of cytochromes P450 and b 5 the following plasmids were used: pCWori+CYP17Horse [17], pCWori+CYP17Human [17], pCWori+CYP17gpig [17], pCWori+P4503A4 [12], pCWori+Mc b 5 rat [18], pCWori+b 5 Om rat [19], pT7 b 5 om2 [19], pT7 b 5 om3 [19], pT7 b 5 Om human [20] and pOR262P450red [21].…”
Section: Chemicalsmentioning
confidence: 99%
“…The purity of protein samples of cytochrome b 5 were analyzed by gel electrophoresis in a 15% polyacrylamide gel under denaturing conditions [22] on a Mini Protean II instrument (Bio Rad, USA). The concentration of the purified b 5 was determined from the absolute absorption spectrum of the oxidized form of the heme protein (ε 413 = 117 mM -1 ·cm -1 ) [23]. Titration of CYP3A4 by various forms of cytochrome b 5 .…”
Section: Chemicalsmentioning
confidence: 99%